Assessment of safety and economic impact of boil-off-gas in LPG storage tanks - Princewill, Nwadinobi Chibundo; Ubasom, Kanu Allwell; David, Chukwudi Onyebuchi (ASCEE, 2023)
This study was carried out to assess the effect of boil-off gas (BOG) on the safety and economic effectiveness of LPG storage tanks. It includes analysis of the thermodynamic properties of LPG; heat absorbed from ambient air by the storage tank that leaks into the LPG, and consequently generates boil-off gas in the supply chain, by utilizing appropriate thermodynamic and heat transfer equations. Analyzing the heat leakage required the estimations of the convective heat transfer coefficient of the ambient air in the supply location and the LPG supply chain, which amounted to 3335.9W/m2K and 21.058W/m2K, respectively, in the system under study. Analyzing the thermodynamic properties, such as specific volume, entropy, and enthalpy of the LPG, shows that the entropy of LPG in the storage tank is negative, which suggests an endothermic process, validating that heat is added to the system from the surroundings. The heat absorbed in the LPG from the ambient air by the storage tank amounted to 1.785kW. The boil-off generation rate due to the storage tank heat leakage was 0.0049kg/s, which translates to a cost equivalent loss of 0.0069/s at an LPG selling price of 1.42/kg. It was recommended that maintenance of insulation and other external factors such as wind speed, solar radiation, ambient temperature, and thermal conductivity of the storage tank material are key factors in minimizing the heat leaks into LPG; hence BOG generation, which is of utmost importance in ensuring safety and economic loss in the LPG supply chain.